EVOLUTION OF NEW PHRASEOLOGICAL UNITS IN THE ERA OF DIGITIZATION (Scientific journal of the Fergana State University, 2024)
The article discuss that, in the digital era, the Internet has become a vast and intricate communication network, giving rise to a unique linguistic phenomenon known as "neo-phraseology" or "computer phraseology." This branch of linguistics examines new, non-standard expressions that emerge from online interactions and become part of the evolving language landscape. Scholars like Crystal and Herring highlight the organic nature of this development, tracing its roots to early online communities and the constraints of digital communication. The study of Internet phraseology reveals how traditional idioms, documented in sources like the "Oxford Dictionary of Idioms," are adapted for digital contexts. Examples include IT-specific terms such as "drop the ball" and "eat your own dogfood," as well as social media phrases like "Facebook official" and "Twitter egg." These innovations reflect the need for brevity, humor, and creativity in online discourse. Furthermore, Internet phraseology demonstrates the interplay between traditional language and digital culture, with expressions crossing over between these realms. The sociocultural implications of this linguistic evolution are profound, affecting communication, culture, and identity. As Internet phraseology continues to evolve, promoting digital literacy and understanding is essential, supported by educational initiatives and ongoing research to navigate the dynamic language landscape of the digital world.